2010
DOI: 10.1002/jcp.22323
|View full text |Cite
|
Sign up to set email alerts
|

Selective regulation of UGT1A1 and SREBP‐1c mRNA expression by docosahexaenoic, eicosapentaenoic, and arachidonic acids

Abstract: We evaluated, in human cell line HepG2, the action of individual dietary polyunsaturated fatty acids (PUFAs) on the expression of several lipid metabolism genes. The effects of docosahexaenoic acid, 22:6, n-3 (DHA), eicosapentaenoic acid, 20:5, n-3 (EPA), and arachidonic acid, 20:4, n-6 (AA) were studied alone and with vitamin E (Vit.E). DHA, EPA, and AA down-regulated mRNAs and encoded proteins of stearoyl-CoA desaturase (SCD) and sterol regulatory element binding protein (SREBP-1c), two major factors involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 40 publications
(60 reference statements)
4
21
1
4
Order By: Relevance
“…Our data show that hypercholesterolemic sera are able to reduce mRNA expression of this lipid-related transcription factor. This finding is in agreement with our previous data where individual pure fatty acids such as DHA, EPA, and AA directly administered on the same liver cell culture induced a down regulation of SREBP-1c [Caputo et al, 2011]. Our data in Figure 3 show that higher levels of AA and LA correspond to elevated gene expression of UGT1A1.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data show that hypercholesterolemic sera are able to reduce mRNA expression of this lipid-related transcription factor. This finding is in agreement with our previous data where individual pure fatty acids such as DHA, EPA, and AA directly administered on the same liver cell culture induced a down regulation of SREBP-1c [Caputo et al, 2011]. Our data in Figure 3 show that higher levels of AA and LA correspond to elevated gene expression of UGT1A1.…”
Section: Discussionsupporting
confidence: 93%
“…Other data show that UGT1A1 induction by pro-inflammatory molecules (such as AA and LA) might represent a key adaptive response to cellular oxidative stress that defends against a variety of detrimental stimuli [Yueh and Tukey, 2007], as in our condition, for example, UGT1A1 expression could be influenced by hypercholesterolemic serum samples. The additional role of inflammatory factors, present in these sera within hypercholesterolemic status, could explain the different result of our previous data in which individual fatty acids reduced UGT1A1 mRNA [Caputo et al, 2011].…”
Section: Discussioncontrasting
confidence: 92%
“…Regarding SREBP, Caputo et al (2010), using PPARα antagonist, argued that an effect of EPA/DHA on SREBP-1c expression is not mediated through PPARα action. On the other hand, Fernandez-Alvarez et al (2011) reported that PPAR/RXR heterodimer activated SREBP-1c promoter and a PPARα agonist increased SREBP-1c expression in the rat liver.…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al (2011) found a decrease of an amount of both the precursor and the nuclear SREBP-1 protein in their experiment. It is worthy to mention in this context an effect of concentration: Caputo et al (2010) reported a decrease of both SREBP-1 mRNA and SREBP-1 protein in human hepatoma treated with EPA/DHA, but only in concentration of 50μM and not in concentration of 25μM.…”
Section: Discussionmentioning
confidence: 99%
“…Se ha observado que el ácido docosahexaenoico (22:6 n-3, DHA) y el ácido eicosapentaenoico (20:5 n-3, EPA) ejercen su acción a través de la interacción con receptores del tipo PPAR, HNF-4, LXR, RXR y SREBP 1c, con lo cual generan respuestas reguladoras (35). El DHA está estrechamente relacionado con la protección del sistema nervioso ya que a través de la activación del PPAR-γ disminuye la producción de…”
Section: Efecto De Los Nutrientes Sobre Los Factores De Transcripcionunclassified